Just another bandwagon? A critical look at the role of the high performance workplace as vehicle for the UK high skills project - Lloyd, C; Payne, J (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2004)
A number of commentators involved with the UK policy debate in skills have recently argued in favour of an active role for government in helping to diffuse the model of the high performance work organisation (HPWO). More specifically, the HPWO is said to offer an environment in which skills and knowledge can be developed on a continuous basis and utilised to full effect. For these commentators, part of the model's attraction lies in its potential to shift the current policy debate beyond its narrow emphasis on boosting the supply of skills and qualifications as the main route to developing a high skills economy in the UK. The paper argues that there has been tendency for academics from the vocational education and training community to 'buy into' the high performance work model too uncritically without interrogating its key assumptions. A closer engagement with the critical literature surrounding the HPWO suggest that its implications for skills and employees are uncertain and may, in some cases, be negative. The paper questions, therefore, whether the HPWO should be seen as a suitable vehicle for a high skills project in the UK and asks whether it might be time to re-focus attention on the more fundamental issue of how to develop high skilled, high quality employment whilst also improving work and employment conditions for employees in general.